Planning for the Development of Danau Biru Geotourism in North Kolaka - Taslim Fait; Irabiah Irabiah; Juslan Badia; Anis Ribcalia Septiana (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
This article analyzes the local government's planning in the development of Danau Biru Geotourism in Walasiho Village, North Kolaka Regency, as an effort to realize sustainable tourism destinations based on local potential. Using qualitative methods, data was obtained through in-depth interviews, field observations, and focus group discussions with informants from local governments, village governments, business actors, and visitors, supplemented by secondary data from official documents and related publications. The analysis was carried out using the managerial planning framework of George R. Terry (2008) which includes goal setting, condition evaluation, identification of supporting and inhibiting factors, and preparation of development plans. The results of the study show that the planning has accommodated the needs and available resources, such as the uniqueness of the Danau Biru, community support, and development master plan. However, implementation is constrained by limited infrastructure, funding, and management capacity. Supporting factors include natural attraction, adequate accessibility, and increasing trend of visits, while inhibiting factors include lack of facilities, lack of promotion, and lack of optimal private partnerships. The management of Danau Biru has been carried out through an annual cooperation agreement between the North Kolaka Tourism Office and the Walasiho Village Joint Enterprise. The conclusion of the study emphasizes the need for a sustainable strategy that combines the development of basic facilities, institutional strengthening through the formation of tourism awareness groups, integrated promotion, and cross-sectoral collaboration, as well as integration with surrounding destinations to increase the attractiveness and economic contribution of the destination.